1983
DOI: 10.1159/000260714
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Streptococcus mutatis and Its Relationship to Caries in a Child Population over 2 Years

Abstract: The natural history of Streptococcus mutans was studied in occlusal fissures of 238 right and 235 left lower mandibular first molars in 279 children, initially aged 6–7, over a 2-year period. S. mutans infection was endemic in this group. Results showed that the levels of S. mutans were fairly stable – an initially high level of infection tended to stay high, and vice versa. High levels of infection were more associated with subsequent development of caries. None of the 21 teeth with nondetectable levels of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 2 publications
(3 reference statements)
3
22
0
2
Order By: Relevance
“…Two of these requirements involve niche creation by earlier colonizers, such as the MS and/or other cariogens. The concept that "S. mutans may be necessary for fissure caries, though not a sufficient condition" (Burt et al 1983) is consistent with our model (Fig. 2) because MS are present in both cariesfree and caries-active sites.…”
Section: Model For the Role Of Lactobacilli In Dental Cariessupporting
confidence: 87%
“…Two of these requirements involve niche creation by earlier colonizers, such as the MS and/or other cariogens. The concept that "S. mutans may be necessary for fissure caries, though not a sufficient condition" (Burt et al 1983) is consistent with our model (Fig. 2) because MS are present in both cariesfree and caries-active sites.…”
Section: Model For the Role Of Lactobacilli In Dental Cariessupporting
confidence: 87%
“…In our previous paper [Burt et al, 1983] absolute counts were employed whereas we used proportions in this paper. Use of counts can be criticized because they can fluctuate with the amount of plaque re moved in the sample; proportions of total bacteria should be independent of plaque quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the explana tions given for these observations is the possibility that other coinhabiting plaque species modify the cariogenic potential of S. mutans [Loesche, 1982;Bowden et al, 1984], Several investigators have found that a high S. mutans to Streptococcus san guis ratio is highly associated with the de velopment of caries [de Stoppelaar et al, 1969;Loesche and Straffon, 1979;Burt et al, 1983] and that lactobacilli may be associated with some carious lesions [Loesche and Straffon, 1979;Bowden et al, 1984], But apart from these observations, no study, except that carried out by Hardy et al [1977], has examined the relationship of various plaque organisms to each other, their relative numerical stability over time, and the relationship between the relative proportions of coinhabiting bacterial spe cies to the subsequent development of ca ries.…”
mentioning
confidence: 99%
“…In another study, however, a cariespredictive role for the S. mutans/S. sanguinis ratio could not be demonstrated (3).…”
mentioning
confidence: 86%